(untitled) (El-Wahat Journal for Research and Studies, 2025)
Industrial Property Rights Concern All Ideas And Creativity Produced By The Mind, And Distinguished Creations In The Field Of Industrial And Commercial Inventions And Innovations, As It Give Its Owner Right To Use Exploit And Dispose Of It ,And Its Connection With Elements Of The Legal Property Related To The Foreign Investor Upon The Establishment Of The Investment Project, The Algerian Legislature Issued Several Legal Texts That Guarantees Adequate Legal Protection Investment Projects From The Risk Of Assault Of Industrial Property Elements The Foreign Investor. The Aim Of This Study Is To Highlight The New Investment Vision Adopted By The Algerian Legislator In The Through New Investment Law No22/18, Which Aims To Restructure The Incentive Systems For Investment And The Improvement Of The Guarantees And Protections Provided For Foreign Capital, That It Strengthening Intellectual Industrial Property Right Systems This Will Encourage Investment And The Volume Of Investments, Who Constitute A Real Basic Cause To Increase Capital And Attract Several New Technologies In Order To Relater The Economy And Develop. Key Words: Industrial Property Right; Foreign Investor; Legal Protection; Treaty Of Paris; Trips Agreement; Tradition, Unfair Competition.